Pengaruh Pengetahuan, Kesadaran Dan Pendapatan Masyarakat Terhadap Perilaku Membayar Zakat Mal Di Desa Sikapas Mandailing Natal - Antika Fitri, Sri Sudiarti, Nurul Jannah (Journal Economy and Currency Study (JECS), 2022)
This study was conducted with the aim of analyzing the influence of knowledge, awareness and income on people's behavior in paying zakat malls in Sikapas Mandailing Natal Village. This research was motivated by irregularities in the practice of paying zakat malls in Sikapas Mandailing Natal Village, one of the irregularities was that at the time of zakat payments, muzakki mall did not clearly state the amount of nishab of property based on the source of the property owned to mustahiq zakat. This research method was carried out with a total sample of 100 respondents determined by the calculation technique proposed by Slovin with the purposive sampling method by distributing questionnaires to respondents by distributing them directly. The analytical techniques used are data quality test, classical assumption test, multiple linear regression analysis and hypothesis test using the SPSS version 22 program. The results of the analysis in this study showed that knowledge had a positive and significant effect on the behavior of paying zakat malls, awareness had a positive and significant effect on the behavior of paying zakat malls, and income variables did not affect the behavior of paying zakat malls. The percentage of the influence of the variables of knowledge, awareness and income on people's behavior in paying zakat malls together was 72%.